A new radiographic finding of adult symptomatic discoid lateral meniscus. Issue 14 (April 2020) - Lu, Xin; Qian, Jun; Yang, Bo; Li, Zheng; Fan, Yu; Jiang, Bo
Abstract : Abstract: Discoid lateral meniscus is one of the most common knee problems in clinical practice. Several radiographic findings have been reported to screen discoid lateral meniscus, but the diagnostic value of those signs varies. We introduce a new method of measurement on plain radiograph for initial screening discoid lateral meniscus and describe its efficacy and correlation to symptomatic discoid lateral meniscus. This is a retrospective case-control study. Seventy-eight arthroscopic proven symptomatic discoid lateral meniscus adult patients plus 73 patients of matched control group were retrospectively reviewed at our institution between 2012 and 2017. We studied their standardized non-weight-bearing knee radiograph anterior-posterior view and measured the following parameters: lateral joint space height, lateral tibia spine height, fibular head height, lateral tibia plateau obliquity (LTPO), and lateral condyle convex angle (LCCA). Significant statistical differences were found in the lateral joint space height, lateral tibia spine height, fibular head height, LTPO and LCCA measurements between the 2 groups ( P < .05). Also, we found the phenomenon that angle parameters such as LTPO and LCCA had high sensitivities with relatively low specificities compared with height parameters. We propose that LCCA is a new measurement which is statistically larger in discoid meniscus patients. Furthermore, it can be useful for screening discoid lateral meniscus on plain radiograph with its relative high sensitivity. Level of Evidence: Level III, Case-control study.